{x+4y/9 - x-2y/3 = 0 {x+7y/4 + x+y/6 = 4

olenkazyateva olenkazyateva    2   27.09.2019 06:40    1

Ответы
арсюха6 арсюха6  08.10.2020 22:09
\frac{x + 4y}{9} - \frac{x - 2y}{3} = 0 \\ \frac{x + 7y}{4} + \frac{x + y}{6} = 4 \\ \\ x + 4y - 3(x - 2y) = 0 \\ 3(x + 7y) + 2(x + y) = 48 \\ \\ x + 4y - 3x + 6y = 0 \\ 3x + 21y + 2x + 2y = 48 \\ \\ - 2x + 10y = 0 \\ 5x + 23y = 48 \\ \\ 2x = 10y \\ 5x + 23y = 48 \\ \\ x = 5y \\ 5x + 23y = 48 \\ \\ x = 5y \\ 25y + 23y = 48 \\ \\ x = 5y \\ 48y = 48 \\ \\ y = 1 \\ x = 5y \\ \\ y = 1 \\ x = 5
ответ: (5; 1)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика